Challenges in Sustainable Supply Chain Management of Live Animal Trading: A Case Study of Live Animal Industry in Malaysia - Suzari Abdul Rahim; Aidi Ahmi; Nor Aida Abdul Rahman (International Journal of Supply Chain Management, 2020)
There are various challenges of the live animal industry, not just in Malaysia but also to many parts of the world. This study focuses on the supply chain management of live animal trading in Malaysia. This study aims to investigate the challenges specifically in supply chain management areas in the live animal trading. A total of 20 semi-structured interviews have been carried out with a few companies involved in the industry and a few officers from the Malaysian Quarantine and Inspection Services (MAQIS). The premises of the companies also have been observed a day earlier before the interview. The data gathered from the observation as well as from the interview and literature review were analysed using TOWS analysis. The findings show that the industry is facing multiple challenges based on their strengths and weaknesses as well as the opportunities that being offered and the threats that they faced, which are vital for their business continuity.  This study also highlights the essential problems to focus on and formulate strategies to achieve competitive advantages and sustainable supply chain management, especially to the practitioners in the live animal trading industry.